EVALUASI KEWAJARAN HARGA DAN KESESUAIAN METODE TRANSFER PRICING DENGAN PERDIRJEN PAJAK NOMOR PER-32/PJ/2011 (STUDI KASUS PADA PT. MERTEX INDONESIA) - Saraswati, Medianti Jipi (Jurnal Mahasiswa Perpajakan, 2014)
PT. MERTEX using Transactional Net Margin Method as a pricing method in transfer pricing transactions with related parties. Related to this method, needs to be applicated Arm’s Length Principles as defined in PER-32/PJ/2011. This study used a descriptive research with a qualitative approach based on case studies. The results showed that, transfer pricing methods used by PT. MERTEX in accordance with the Arm’s Length Principles and PT. MERTEX has implemented procedures and measures, as stipulated in PER-32/PJ/2011. There are differences between PT. MERTEX and Directorate General of Taxes Auditor in the disclosure of arm’s length price on transfer pricing transaction, so it needs to be continued to the Objection level. Documentation of PT. MERTEX’s transaction with related parties needs to be continued to meet the requirements in applying the Arm’s Length Principles as defined in PER-32/PJ/2011. If PT. MERTEX can show that documents in case of investigation by the Director General of Taxes Auditor, PT. MERTEX have strong evidence to support his argument in applying the arm’s length price/ earnings, thus PT. MERTEX able to resolve their disputes with the Auditor until the Appeals level. Keyword: Transactional Net Margin Method, Transfer Pricing, Related Party, Arm’s Length, PER-32/PJ/2011